O43-2 Development of a barcode-based exposure assessment method to evaluate occupational exposure to cleaning products and disinfectants. (1st September 2016) - Quinot, Catherine; Amsellem-Dubourget, S; Temam, S; Sévin, E; Barreto, C; Felicite, J; Siroux, V; Girard, R; Descatha, A; Moual, NLe; Dumas, O
Abstract : Introduction: Exposure to cleaning products and disinfectants is a risk factor for respiratory diseases. Assessment of exposure to cleaning products, which are complex mixture of many chemicals, remains a challenge. We aimed to develop an innovative tool using a smartphone application and barcodes to improve the assessment of occupational exposure to cleaning products. Methods: Four steps have been defined for the development of this tool: (1) development of a database of cleaning products and disinfectants used in French hospitals with their barcodes and active ingredients, using documentation from infection control expert networks, national regulatory agencies, and industrials; (2) development of a smartphone application and its related backend to successively scan barcodes of products used weekly and fill a short questionnaire to record the product name, frequency of use, type of product, use of protection, etc.; (3) test the smartphone application to collect information on products actually used in several hospital departments. We will also evaluate the added value of the proposed tool to assess occupational exposure to cleaning products and ease of use of the application; (4) evaluate the completeness rate of the database by comparing products in the database and products used in hospitals. Results: The development of the database is underway. Precise information (barcodes, ingredients, type of use and safety data sheet of the products) are available through ProdHyBase®, a non-exhaustive database of disinfectants and hand hygiene products (http://www.prodhybase.fr ), for about 700 products. To improve completeness of the database, we add information available on specific regulatory agencies websites (http://simmbad.fr/ ) and industrials' websites. The development of the smartphone application is in progress. Conclusion: This innovative and easy-to-use method should improve the assessment of occupational exposure to cleaning products in epidemiological studies. It will contribute to enhance health risk assessment and to the development of preventive strategies. Grants: Anses-PNR-EST-2015-1-022/Ademe-1594C0091;IRESP;Univ Paris-Sud;UVSQ